2011
DOI: 10.1111/j.1399-0012.2011.01489.x
|View full text |Cite
|
Sign up to set email alerts
|

Self‐reported non‐adherence to immune‐suppressant therapy in liver transplant recipients: demographic, interpersonal, and intrapersonal factors

Abstract: Adherence to immune suppressants and follow-up care regimen is important in achieving optimal long-term outcomes after organ transplantation. To identify patients most at risk for non-adherence, this cross-sectional, descriptive study explores the prevalence and correlates of non-adherence to immune-suppressant therapy among liver recipients. Anonymous questionnaires mailed consisted of the domains: (i) adherence barriers to immune suppressants, (ii) immune suppressants knowledge, (iii) demographics, (iv) soci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
51
1
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 48 publications
(57 citation statements)
references
References 42 publications
(86 reference statements)
4
51
1
1
Order By: Relevance
“…This finding is consistent with high rates of self-reported non-adherence in transplant recipients [6,21]. In a single-center US study, 56 % of transplant recipients reported non-adherence within the 2-5 year post-transplant period [14]. Various international studies have reported rather low rates of non- adherence among liver transplant recipients [12], which may be attributed to differences in methodology and social factors (i.e., differences in access to medical care and medications in US vs. non-US health care systems).…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…This finding is consistent with high rates of self-reported non-adherence in transplant recipients [6,21]. In a single-center US study, 56 % of transplant recipients reported non-adherence within the 2-5 year post-transplant period [14]. Various international studies have reported rather low rates of non- adherence among liver transplant recipients [12], which may be attributed to differences in methodology and social factors (i.e., differences in access to medical care and medications in US vs. non-US health care systems).…”
Section: Discussionsupporting
confidence: 91%
“…These behaviors are commonly used in the clinical setting to predict adherence, and our study substantiates this practice. Missed office appointments has been shown to be correlated with IS therapy non-adherence, which was confirmed in this study [14]. Pre-transplant substance abuse and non-adherence were found to be significantly associated with post-transplant non-adherence as measured by chart evidence.…”
Section: Discussionsupporting
confidence: 77%
See 3 more Smart Citations